Distribuição da área específica foliar no perfil vertical do dossel florestal da bacia do Rio Cueiras, Manaus - AM - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This study aims to understand how the specific leaf area (SLA) was distributed at vertical profile of tropical forest. The research was conducted at the Experimental Station for Tropical Forest research (ZF-2) of the National Institute of Research of the Amazon (INPA). This study used five towers to access each height of the vertical profile of canopy, where 1090 fully expanded leaves collected and carry to laboratory to determine SLA. Area and dry mass of these leaves were evaluated by using leaf area integrator and analytical balance, respectively. The SLA was determined by ratio of leaf area for its mass and SLA was expressed in cm2.g-1. The results showed that there was negative correlation (r2 = 0,62, P < 0,0001) between height of canopy vertical profile and SLA and this correlation can be described by equation SLA = Exp(2,202 – 0,015 Height) and the it can verify a stratification in this vertical profile, where it was found three different classes of height, the lowest height at 0 to 10 m presented the higher mean value of SLA, at 10 to 20 m the intermediate mean values of SLA were verified and higher than 20 m it was observed the lowest SLA mean values at canopy vertical profile.
Keywords: Área específica foliar; Floresta amazônica; morfologia foliar; CNPQ:: CIÊNCIAS HUMANAS